2015
DOI: 10.1007/s00787-015-0784-3
|View full text |Cite
|
Sign up to set email alerts
|

The influence of comorbid oppositional defiant disorder on white matter microstructure in attention-deficit/hyperactivity disorder

Abstract: Attention-deficit/hyperactivity disorder (ADHD) and oppositional defiant disorder (ODD) are highly comorbid disorders. ADHD has been associated with altered white matter (WM) microstructure, though the literature is inconsistent, which may be due to differences in the in- or exclusion of participants with comorbid ODD. WM abnormalities in ODD are still poorly understood, and it is unclear whether comorbid ODD in ADHD may have confounded the current ADHD literature. Diffusion Tensor Imaging (DTI) was used to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…ADHD with frequent comorbidity on ODD was associated with alterations in GMV of orbitofrontal cortex, the superior frontal gyrus, middle frontal gyrus, and the inferior parietal gyrus (64) and FA of inferior fronto-occipital fasciculus, corticospinal tract, forceps minor, and internal capsule (65). In addition, ADHD is closely related to the dysfunction of frontal-striatalcerebellar circuits (66).…”
Section: More Sensitive Brain Age-based Analysesmentioning
confidence: 99%
“…ADHD with frequent comorbidity on ODD was associated with alterations in GMV of orbitofrontal cortex, the superior frontal gyrus, middle frontal gyrus, and the inferior parietal gyrus (64) and FA of inferior fronto-occipital fasciculus, corticospinal tract, forceps minor, and internal capsule (65). In addition, ADHD is closely related to the dysfunction of frontal-striatalcerebellar circuits (66).…”
Section: More Sensitive Brain Age-based Analysesmentioning
confidence: 99%
“…The ratio of psychiatric comorbidity in our ASD group (Supplementary Table 1) is largely compatible with the previous literature 91 . Nonetheless, this caveat regarding inclusion criteria may influence the present results, as ADHD is also highly associated with impaired self-regulation 92,93 . Furthermore, the concurrent use of methylphenidate might also have effects on the WM microstructure 94 .…”
Section: Discussionmentioning
confidence: 84%
“…Although only a few small studies distinguished ADHD CD+ from ADHD ODD+ , most of them still revealed a significant difference between ADHD CD+ and ADHD ODD+ . For example, van Ewijk et al found that comorbid ODD is associated with altered WM microstructure, and there was an interaction between ODD and (subclinical) CD, which indicated that ODD and CD should be treated as separate constructs [ 40 ]. This again illustrates that comorbid ODD and comorbid CD are different in children with ADHD.…”
Section: Discussionmentioning
confidence: 99%